Disclosure of wrongdoings and protection of employee whistleblower - Ali Mohamed, Ashgar Ali (2015)
This presentation addresses on employee whistleblower protection with reference to the Malaysia law and the laws in the commonwealth jurisdictions. The paper propose various changes to be included to the Malaysia law so as to accord protection specifically to employee whistleblower.